Sample version 2.0 ITS_LIVE Sentinel-1 image pair product of ice velocity in Greenland - Yang Lei; Alex Gardner; Piyush Agram (Zenodo, 2021)
21 samples ofversion 2.0 ITS_LIVE Sentinel-1 image pair productof ice velocity in three test regions of Greenland Ice Sheet Sensor: Sentinel-1A/B Processor: ISCE v2.4.1 (topsApp -> Geogrid v1.4.0-> autoRIFT v1.4.0) Project: NASA MEaSUREs project ITS_LIVE Region 1 (69.13N, 50.88W; Jakobshavn Isbræ Glacier): 7 ascending image pairs Region 2(77.61N, 42.79W; central north of interior Greenland): 3 ascendingimage pairs Region 3(72.48N, 35.87W; central south of interior Greenland): 10 descendingimage pairs and 1 ascending image pair This serves as asupplementary dataset for the companion journal article submitted to Earth System Science Data (to appear soon). Acknowledgement: This effort was funded by the NASA MEaSUREs program in contribution to the Inter-mission Time Series of Land Ice Velocity and Elevation (ITS_LIVE) project ( https://its-live.jpl.nasa.gov/ ) and through Alex Gardner’s participation in the NASA NISAR Science Team